A coupled simulation and fuzzy-rule-based method for assessing health risks at a petroleum-contaminated site. (29th June 2011) - Yang, Aili; Huang, Guohe; Qin, Xiaosheng
Risk assessment of contaminated sites is crucial for evaluating adverse health impacts on local communities, and provides effective decision support for site-remediation practices. In this study, a coupled simulation and fuzzy-rule-based method was proposed for health risk assessment of groundwater contamination, and applied to a petroleum contaminated site. Benzene concentrations under two remediation scenarios (i.e., natural attenuation and pump-and-treat remediation) at different time intervals (1, 10, 20, 30, and 60 years later) were examined. The obtained benzene concentrations were then used to quantify the health risks through the excess lifetime cancer risk (ELCR) model. The study results indicated that the proposed method was useful for assessing potential human health effects when the groundwater was used for drinking water purpose and could effectively identify variation of risk levels under different remediation scenarios. The study also found that the dissolved oxygen was the most thermodynamically favoured electron accepter used in the biodegradation of petroleum hydrocarbons. When implementing remediation actions, we can inject oxygen to subsurface to strengthen aerobic biodegradation process (i.e., air sparging).